Examining the health disparities research plan of the National Institutes of Health : unfinished business - Thomson, Gerald E.; Mitchell, Faith, 1952-; Williams, Monique (National Academy Press, 2006)
In the United States, health among racial and ethnic minorities, as well as poor people, is significantly worse than the overall U.S. population. Health disparities are reflected by indices such as excess mortality and morbidity and shorter life expectancy. Examining the Health Disparities Research Plan of the National Institutes of Health is an assessment of the National Institutes of Health (NIH) Strategic Research Plan and Budget to Reduce and Ultimately Eliminate Health Disparities. It focuses on practical solutions to remedy the state of the current health disparity crisis.